1962
DOI: 10.1139/v62-202
|View full text |Cite
|
Sign up to set email alerts
|

Periodate-Oxidized Phosphomannan Y-2448: Structural Significance of Its Reaction With Alkali

Abstract: Informatioli regarding branching in this macromolecular polysaccliariclc derivative was not established. 'l'lie periodate-oxidatiori product i~eutralized dilute allcali rapidly a t p H 8.5-10.0, with climination of about :30yG of the phosphorus a s inorganic orthophosphate. :\bol~t 80'ji inorganic orthophosphate \\.as obtained b y longer treatment a t pI-I 10.1-10.5. Thcse observations arc shown to support t h e hypothesis t h a t diesterorthophosphatc groups (0.30 mole/molc mannosc u~~i t ) arc held betwecn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1962
1962
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 13 publications
(9 reference statements)
2
13
0
Order By: Relevance
“…The implications of this structure are extracellular phosphomannans, thus indicating the destruction of mannose 6-phosphate residues by periodate treatment. Jeanes & Watson (1962) concluded that these observations supportedthehypothesis that diester phosphate groups were held between C-6 of mannose units otherwise linked through C-1, and C-1 of mannose units which in turn had a mannosidic attachment at C-2. A structure was proposed in which the phosphate groups cross-linked oligosaccharide chains containing 1,2-and 1,3-linked mannose units.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…The implications of this structure are extracellular phosphomannans, thus indicating the destruction of mannose 6-phosphate residues by periodate treatment. Jeanes & Watson (1962) concluded that these observations supportedthehypothesis that diester phosphate groups were held between C-6 of mannose units otherwise linked through C-1, and C-1 of mannose units which in turn had a mannosidic attachment at C-2. A structure was proposed in which the phosphate groups cross-linked oligosaccharide chains containing 1,2-and 1,3-linked mannose units.…”
supporting
confidence: 55%
“…The phosphomannan (0.1 %, w/v) was oxidized by sodium metaperiodate (7.4mM) buffered in 0.5Mammonium acetate buffer, pH 5 (I00ml), and in I00ml of unbuffered solution, in the dark at 4°C. These conditions limit over-oxidation (Jeanes & Watson, 1962). Periodate uptake was measured, on a portion (5 ml) from the buffered reaction, by the method of Malaprade (1928).…”
Section: Periodate Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patents have appeared for the production of phosphonomannans from Hansenula holstii (1 92, 193), Hansenula capsulata, Hansenula minuta, Pachyso fen tannophilus, Torulopsis pinus, and Saccharomyces pini ( 1 93). Sixty percent of 2-0-substituted D-mannopyranosyl residues are linked to structure 16 (195). The molecular weight is 16 X lo6, according to light-scattering measurements (194).…”
Section: Phosphonomannansmentioning
confidence: 99%
“…The immunological effect of the removal of two hydroxyl groups from mannose and their replacement by hydrogen was unknown (39). Nevertheless, the serological results gave the correct indication, since a prolonged purely chemical study of the Hansenula phosphomannan by Jeanes and her collaborators (40) showed that 33 per cent the linkages of mannose were between positions 1 and 2 and 47 per cent between positions 1 and 3. Similarly, we could predict from its reactions with antipncumococcal horse scra of Types II and VI (41), that the polysaccharide of Group A hemolytic streptococcus, the group so dangcrous for the human race, would contain at least a part of its high content of rhamnose bound in positions 1 and 3, as is the L-rhamnose in the capsular polysaccharides of these two pneumococcal types (42).…”
mentioning
confidence: 97%